First record of the flotsam tiger beetle genus Cheiloxya Guérin-Méneville, 1855 (Coleoptera: Cicindelidae) from Yungas Forest of Argentina - Rubio, Lucas E.; Roig-Juñent, Sergio; Michat, Mariano C.; Urcola, Juan I. (Zootaxa, 2025)
Cheiloxya Guérin-Méneville, 1855 is reported for the first time from Argentina, in the Southern Andean Yungas, an ecoregion recognized for its exceptional biodiversity and conservation importance. This represents the most southern record for Cheiloxya, extending the distributional range of the genus by about 900 km.